2009
DOI: 10.1128/mcb.00289-09
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of FLASH with Arsenite Resistance Protein 2 Is Involved in Cell Cycle Progression at S Phase

Abstract: FLASH has been shown to be required for S phase progression and to interact with a nuclear protein, ataxia-telangiectasia locus (NPAT), a component of Cajal bodies in the nucleus and an activator of histone transcription. We investigated the role of human FLASH by using an inducible FLASH knockdown system in the presence or absence of various mutant forms of mouse FLASH. While carboxyl-terminal deletion mutants of FLASH, which do not interact with NPAT, can support S phase progression, its amino-terminal delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 31 publications
(48 reference statements)
10
97
1
Order By: Relevance
“…Previous studies by others demonstrated that the endogenous FLASH and NPAT co-immunoprecipitated but failed to determine whether they interact directly or exist in a common complex containing additional proteins (34,50). We now conclude that FLASH and NPAT directly contact each other via their C-terminal regions.…”
Section: C-terminal Domains Of Flash and Yarp Interact With The C Termentioning
confidence: 54%
See 2 more Smart Citations
“…Previous studies by others demonstrated that the endogenous FLASH and NPAT co-immunoprecipitated but failed to determine whether they interact directly or exist in a common complex containing additional proteins (34,50). We now conclude that FLASH and NPAT directly contact each other via their C-terminal regions.…”
Section: C-terminal Domains Of Flash and Yarp Interact With The C Termentioning
confidence: 54%
“…It has been previously shown that down-regulation of FLASH by RNAi in human cells results in a gradual redistribution of NPAT to the nucleoplasm (34,50). Thus, NPAT on its own is not able to form HLBs in human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NM_009812.2). The oligonucleotides of shRNA for silencing lacZ (32), and for silencing ATG7 (23) were previously described. For the specific knockdown of RIP3, shRNA for mouse RIP3 was generated from nucleotides 413 to 431 of RIP3 cDNA (GenBank TM no NM_019955.2).…”
Section: Methodsmentioning
confidence: 99%
“…It participates in TNF-alpha-induced blockade of glucocorticoid receptor transactivation at the nuclear receptor coactivator level, upstream and independently of NF-kappa-B (Kino and Chrousos, 2003). It also contributes to cell cycle progression at S phase (Kiriyama et al, 2009;Barcaroli D et al, 2006).…”
Section: Functionmentioning
confidence: 99%